2006
DOI: 10.1016/j.cardiores.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin improves left ventricular function after myocardial infarction in hypercholesterolemic rabbits by anti-inflammatory effects

Abstract: Hypercholesterolemia further impaired the depressed LV function in rabbits post-MI. Statin treatment reversed this effect, and conferred additional protection, as in normocholesterolemic animals. Our study suggests that anti-inflammatory and anti-oxidative effects of simvastatin substantially contribute to its beneficial effects on cardiac function after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
6
13
0
Order By: Relevance
“…Pearson's correlation coefficients between PCO and GSH levels in heart tissue of the cholesterol-fed rabbits (r = À0.843, P = 0.002) are shown in Figure 2. Consistent with our previous work as well as with other reports [11][12][13][14][15], the present study demonstrated that the coexistence of severe hypercholesterolemia enhanced oxidative stress and atherogenesis in the cholesterol-rich diet-induced model. As it was expected, the hypercholesterolemic diet group had higher TC and LDL levels than the normal-diet group.…”
Section: R E S U L T Ssupporting
confidence: 93%
See 1 more Smart Citation
“…Pearson's correlation coefficients between PCO and GSH levels in heart tissue of the cholesterol-fed rabbits (r = À0.843, P = 0.002) are shown in Figure 2. Consistent with our previous work as well as with other reports [11][12][13][14][15], the present study demonstrated that the coexistence of severe hypercholesterolemia enhanced oxidative stress and atherogenesis in the cholesterol-rich diet-induced model. As it was expected, the hypercholesterolemic diet group had higher TC and LDL levels than the normal-diet group.…”
Section: R E S U L T Ssupporting
confidence: 93%
“…These results were consistent with previous findings [13][14][15][16][17][18][19][20] and further supported the concept of the pleiotropic vascular protection effects of atorvastatin in hypercholesterolemia. Atorvastatin treatment caused a decrease in MDA, whereas the high-cholesterol diet increased MDA of blood and heart tissue in cholesterol-rich diet-induced rabbits.…”
Section: R E S U L T Ssupporting
confidence: 93%
“…). There were 18 studies on mice , 61 on rats , and 41 on rabbits . This corresponds to 66 (55%) prospective controlled trials and 54 (45%) randomized controlled trials (RCTs).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from their lipid-lowering capabilities, statins seem to have multiple other effects, including a reduction of systemic inflammation [17] and alleviation of myocardial oxidative stress [18], which do not appear to be dosedependent [19]. Also, they modulate endothelium-derived factors [20].…”
Section: Statins and Inflammationmentioning
confidence: 99%